Evolution of the legislation on native languages ​​in Peru - Reyes Malca, Johanna (2014)
This article aims to present an outlook of the evolution of Peruvian legislation about native languages, beginning with Quechua as an official language to finish with the present law intended to preserve native languages all around the Peruvian territory. We would also like to attract attention to the real situation of disregard that native peoples have to go through in everyday life. We are sure this situation can be overcome if clear and well ruled laws intending to support native languages are passed.